Response of laying performance of KUB chicken to dietary protein given during growing period - Cecep Hidayat; S. Iskandar; T Sartika (Jurnal Ilmu Ternak dan Veteriner, 2011)
One hundred and sixty KUB pullets of 22 weeks of age (KUB = Kampung chicken selected for egg production) were previously raised on different dietary protein level during starter-grower period. During starting period, chicks (0-12 weeks of age) were given dietary protein of: 16% crude protein, CP (R1); 17.5% CP (R2); 19% CP (R3); 20.5% CP (R4); 22% CP (R5). All dietary treatments were iso-energy of 2800 kcal ME (metabolisable energy)/kg. During growing period (12-22 weeks) each group of treatment chick was divided into two regimes of dietary protein levels. One was subjected to the same as treatments given during starting period, and the other one was given diet with reduced dietary protein content up to 1.5%. The treatments were R1-1, having dietary protein of 16.0%; R1-2, having dietary protein of 14.5%; R2-1, having dietary protein of 17.5%; R2-2, having dietary protein of 16.0%; R3-1, having dietary protein of 19.0%; R3-2, having dietary protein of 17.5%; R4-1, having dietary protein of 20.5%; R4-2, having dietary protein of 19.0%; R5-1, having dietary protein of 22% and R5-2, having dietary protein of 20.5%. The energy content of all dietary treatments was the same for all treatments 2800 kkal ME/kg. The hens were then grouped into the treatment as the treatment groups of growing period of 12-22 weeks. Hens were then raised on laying diet, containing 17.11% CP (crude protein) with 2728 kcal ME/kg. The results showed that the change of dietary treatment, given during growing period, influenced (P < 0,05) first lay weight, first egg weight,  weight gain, egg weight, egg width, egg volume of KUB hens age of 22-42 weeks. And the dietary protein treatment, given during starter and growing period, influenced (P < 0.05) first lay body weight, first lay age, feed consumption, egg weight, egg length, egg width of KUB hens age of 22-42 weeks. Key Words: KUB Chicken, Starting and Growing Dietary Protein, Egg Production